2021
DOI: 10.18316/rcd.v13i29.7998
|View full text |Cite
|
Sign up to set email alerts
|

Desafios da in-visibilidade: representações sociais de ciganos em jornais brasileiros e portugueses

Abstract: Tendo em vista o papel dos diversos tipos de mídia na (re)produção de significados acerca de diferentes objetos sociais, este estudo teve, como objetivo, analisar as representações sociais de ciganos em notícias veiculadas por jornais brasileiros e portugueses. No total, foram analisadas 520 reportagens a partir da Classificação Hierárquica Descendente (CHD), e, dessas, 254 que abordavam diretamente os ciganos foram consideradas para a análise de conteúdo. Na CHD, foram identificadas as seguintes classes lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…), there is a certain ideological bias about the concept of being "Gitano" (p. 200). Brasil and Bonomo (2021), when analyzing how Roma have been portrayed in Brazilian and Portuguese newspapers, concluded that these representations "(. .…”
Section: National Public Policies To Combat Antigypsyismmentioning
confidence: 99%
“…), there is a certain ideological bias about the concept of being "Gitano" (p. 200). Brasil and Bonomo (2021), when analyzing how Roma have been portrayed in Brazilian and Portuguese newspapers, concluded that these representations "(. .…”
Section: National Public Policies To Combat Antigypsyismmentioning
confidence: 99%